Peran Komite Audit dan Diversity Gender dalam Memoderasi Hubungan CSR terhadap Nilai Perusahaan - Fatoni, Mohammad Hafid; Suwarno Suwarno (Pajak dan Manajemen Keuangan, 2026)
This study aims to analyze the influence of Corporate Social Responsibility (CSR) on firm value and examine the role of audit committees and gender diversity as moderating variables in raw materials companies listed on the Indonesia Stock Exchange. Using a quantitative approach with a sample of 58 companies selected through purposive sampling, data were analyzed using descriptive statistics and moderated regression analysis (MRA). The results show that CSR has a positive and significant effect on firm value, indicating that the higher the disclosure and implementation of CSR, the higher the market appreciation of the company. However, audit committees and gender diversity were not proven to be able to moderate the relationship between CSR and firm value. This finding implies that although CSR has been proven effective in increasing firm value through positive investor perceptions, corporate governance mechanisms represented by audit committees and gender diversity have not functioned optimally in strengthening this relationship. Therefore, companies need to consistently improve the quality of CSR implementation and evaluate the effectiveness of the role of audit committees and gender diversity policies so that they are not merely regulatory compliance but actually contribute to overseeing and directing the company's sustainability strategy.